1993
DOI: 10.1002/tera.1420480207
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by Tiron (sodium 4,5‐dihydroxybenzene‐1,3‐disulfonate) of vanadate‐induced developmental toxicity in mice

Abstract: Vanadate is embryotoxic and fetotoxic in golden hamsters, mice and rats. Tiron (sodium 4,5-dihydroxybenzene-1,3-disulfonate), a chelating agent widely used in analytical chemistry, is an effective antidote in the treatment of oral or parenteral vanadate poisoning. The present study evaluated the effect of administration of Tiron on sodium metavanadate (NaVO3)-induced developmental toxicity in mice. NaVO3 (25 mg/kg, i.p.) was injected on day 12 of gestation, whereas Tiron was injected subcutaneously at 0, 24, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Vanadium action, as an insulin-like drug widely described by many investigators (15,6,7,8,9,12,13), inspired us to use it in our experiments. Preliminary results of other studies showed biological activity of both forms of vanadium (vanadyl or vanadate) but recent work showed rather the action of vanadyl, and postulating that vanadate is reduced into it within cells (15,21,17,18). The vanadium-oxalate complex (similar to commonly used vanadium derivatives) was reluctantly drunk by the rats and caused diminished fluid consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium action, as an insulin-like drug widely described by many investigators (15,6,7,8,9,12,13), inspired us to use it in our experiments. Preliminary results of other studies showed biological activity of both forms of vanadium (vanadyl or vanadate) but recent work showed rather the action of vanadyl, and postulating that vanadate is reduced into it within cells (15,21,17,18). The vanadium-oxalate complex (similar to commonly used vanadium derivatives) was reluctantly drunk by the rats and caused diminished fluid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs were used usually together with vanadium, lowering its toxicity, especially in animals with streptozotocin (SZ) induced diabetes: the most 0.3%-0.8% NaCI (14,19). The vitamin E, aforesaid lazaroid, V-83836e (20), Tiron (4,5-dihydroxybenzene-1 ,3-disulfonate) (21), deferoxyamine, EDTA, ksylenol orange, base fenantroline (22) were also applied.…”
Section: Introductionmentioning
confidence: 99%
“…Tiron, 4, 5-dihydroxy-1, 3-benzene disulfonic acid, with the water-soluble and cell permeable characteristic, is an effective antioxidant, that can remove all kinds of harmful free radicals [ 11 ]. For example, it can reverse the reactive oxygen species (ROS)-induced cell apoptosis, or act as a nontoxic chelating agent to alleviate the acute toxic metal overload [ 12 ]. Tiron has been reported to be able to inhibit apoptosis in human lung cancer cells induced by bortezomib [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association of vanadate with Tiron, a chelating agent, has been shown to be effective in preventing vanadate poisoning, without altering its glucose lowering ability. 96 The attempts to minimize the toxic effects associated with vanadate treatment are not conclusive. The resolution of these fundamental issues is essential prior to making vanadate a valuable option in the treatment of hyperglycemia.…”
Section: Chemically Active Elementsmentioning
confidence: 99%